EVALUASI PEMBELAJARAN BAHASA INDONESIA MATERI SURAT RESMI DAN PRIBADI MENGGUNAKAN MODEL CIPP DI SMP - Ilman Nafi’an Lubis; Ratri Nindya Agustina; Gisella Orlanova Ramadhani; Wagiran (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to evaluate the implementation of Indonesian language instruction on the topics of formal and personal letters in the 7th grade at SMPN 7 Medan using the CIPP model (Context, Input, Process, Product). This study employs a qualitative descriptive approach with an evaluative research design. Data were obtained through video observations of the learning process and documentation of learning materials, including the In-Depth Lesson Plan (RPM), worksheets (LKPD), learning media, assessments, and student assignment results. The results of the study indicate that in terms of context, objectives, content, activities, and assessment, the teaching aligns with the targeted competencies. In terms of input, the learning tools used by teachers were comprehensive and supported active learning through the Problem-Based Learning (PBL) model and the Deep Learning approach. In terms of process, students were active in discussions, analysis, and presentations, although there were still challenges in time management, classroom management, and support for students who were slow learners. In terms of product, most students were able to identify and analyze formal and personal letters effectively and demonstrated fairly good critical thinking skills. Based on the evaluation results, the implementation of learning has gone quite well and supports active and meaningful learning. However, the development of HOTS assessments, the use of interactive media, and differentiated learning support still need to be improved.